The scandalous sisterhood of Prickwillow Place - Berry, Julie, 1974- (Square Fish, 2016)
In 1890s England, seven Victorian young ladies conspire to hide the murder of their headmistress and her brother from authorities so their boarding school won't be closed. As the girls try to keep the school running without anyone knowing they are there alone, they also try to uncover the real killer before he strikes again.